Digital-Based Human Resource Management Strategy in Developing Teacher Competence Amidst Budgetary Constraints - Sarah Sarah; Fauzan Ahmad Siregar (Continuous Education: Journal of Science and Research, 2026)
Teacher competency development is a crucial factor in improving educational quality; however, many Islamic educational institutions face budget constraints that limit the implementation of sustainable professional development programs. The rapid advancement of digital technology offers opportunities for educational institutions to optimize Human Resource Management (HRM) strategies through digital platforms and Artificial Intelligence (AI) as more effective and cost-efficient alternatives. This study aims to analyze digital-based HRM strategies in developing teacher competence amidst budgetary constraints at SMP Terpadu Bustanul Arifin. A qualitative research approach was employed using observations, semi-structured interviews, and documentation as data collection techniques. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while data credibility was ensured through source and method triangulation. The findings indicate that digital-based HRM strategies enhance teachers' pedagogical, professional, social, and personal competencies through online training, self-directed learning, digital collaboration platforms, and the utilization of AI in instructional planning. Nevertheless, several challenges remain, including limited digital infrastructure, varying levels of teachers' digital literacy, and resistance to technological change. This study concludes that digital-based HRM strategies provide an effective and sustainable solution for improving teacher competence despite financial limitations. The findings imply that educational institutions should strengthen digital transformation policies, enhance teachers' digital capacities, and improve technological infrastructure to support the sustainable improvement of educational quality in Islamic schools.